2004
DOI: 10.1590/s1516-31802004000300009
|View full text |Cite
|
Sign up to set email alerts
|

The role of HER2/neu, BCL2, p53 genes and proliferating cell nuclear protein as molecular prognostic parameters in localized prostate carcinoma

Abstract: One-third of prostate adenocarcinomas express p53 protein, and this characteristic is related to tumor stage. HER2/neu is frequently expressed in prostate carcinomas, with no correlation with histological parameters. BCL2 is rarely expressed, and together with proliferative activity has no relationship with prognostic pathological variables in these neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
3
11
0
3
Order By: Relevance
“…Our findings confirmed the reports of Karaburun et al [28]. But they contradict the observations of Fonseca et al [29] of a positive correlation between p53 expression and both an increasing PSA level and clinical stage. We also noted a significant positive correlation between p53 labeling index and Ki-67 labeling index (R = 0.35, p < 0.005), confirming that the mutated gene p53 protein loses the ability to inhibit cell proliferation.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 78%
“…Our findings confirmed the reports of Karaburun et al [28]. But they contradict the observations of Fonseca et al [29] of a positive correlation between p53 expression and both an increasing PSA level and clinical stage. We also noted a significant positive correlation between p53 labeling index and Ki-67 labeling index (R = 0.35, p < 0.005), confirming that the mutated gene p53 protein loses the ability to inhibit cell proliferation.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 78%
“…In a previous study [21], we evaluated the presence of BCL2 and BAX-expressing cells in cervical lesions, according the degree of lesions, and BCL2 expression was observed mainly in HSIL women when compared with LSIL and control groups, favoring carcinogenesis. In accordance, BCL2 expression was associated with decreased survival in leukemia and prostate cancer [28,29], whereas in colorectal [30,31] and breast cancer, it was related to favorable outcome.…”
Section: Discussionmentioning
confidence: 68%
“…All statistical tests were two-sided, a p value of 0.05 was considered significant, and analyses were performed using Epi Info 6 (Version 6.04, July 1996), SNPStats [29], and SPSS (Version 16, September 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, abnormal bcl-2 or bax expression was not significantly associated with Gleason Score or stage; although a borderline relationship of bax expression to Gleason Score was observed (Table 3). While some relationships of these biomarkers to Gleason Score have been reported (9,(22)(23)(24), this has not been a consistent finding (25)(26)(27). In a report of patients with Stage B, C, or D disease, Amirghofran et al (28) found that bax, but not bcl-2 expression, was significantly related to prostate carcinoma stage (p = 0.031); no correlation to Gleason Score was observed for either biomarker.…”
Section: Discussionmentioning
confidence: 95%